Propuesta conceptual sustentable del diseño de un sistema especializado de prevención de desperdicio de material aprovechable y ayuda para recicladores y entidades de recolección de la ciudad de Bogotá (2021)
Through observation, theoretical review and interaction with recyclers and people in charge of collection centers, the problem of not classifying usable waste was identified, placing the project in a real situation that requires the implementation of new alternatives through technologies with social impact, pedagogies, technical knowledge and awareness of the negative impact of not properly classifying solid waste in ecosystems, this problem is addressed from the industrial design from disruptive and innovative perspectives to generate significant change in societies and communities.